An evaluation of student personality program in secondary schools: a systematic literature review - Mohd Shaleh Mislan; Mohd Isa Hamzah; Khadijah Abdul Razak (Institute of Advanced Engineering and Science, 2026)
The purpose of education is to uplift and develop human personality, morals, behavior, and character. Despite various initiatives and plans, the efforts to cultivate good values and character among students are increasingly challenging due to the negative influence of the local environment as well as the borderless social media. This issue called many researchers to conduct studies to evaluate the implementation of student personality programs in secondary schools, but systematic literature reviews (SLR) on this topic are still limited. Therefore, this study aims to conduct a SLR to evaluate past studies related to the assessment of student character programs. The SLR writing process was according to the preferred reporting items for systematic review and meta-analysis (PRISMA). Two main databases, namely Web of Science (WoS) and Scopus, were used to identify relevant articles and sources. Based on the thematic analysis, four main themes were found, which were behavioral, emotional, cognitive, and social. This study provides a comprehensive overview of the implementation of student character programs, which can serve as an important reference for educators to strengthen character development among secondary school students. These findings are expected to contribute to the development of more effective programs in addressing the challenges of nurturing character among the younger generation in the modern era.